1985
DOI: 10.3354/meps025229
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coelenterate predation on larval plaice Pleuronectes platessa and flounder Platichthys flesus stock in the western Wadden Sea

Abstract: During the seasonal immigration of plaice and flounder larvae into the Dutch Wadden Sea in spring, the coelenterates Pleurobrachia pileus L. and Aurelia aurita L. have been positively identified as predators of both flatfish species. Evidence for a causal relation between outbursts of the predatory coelenterates and the observed abrupt termination of larval flatfish immigration is found in (1) the coincidence of increases in coelenterate numbers and decreases in larval densities, (2) positive observations of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Möller 1980, van der Veer 1985, Arai 1988, Bailey & Houde 1989, Shiganova 1998, virtually no direct comparisons of diet and co-occurrence have been made. Although 2 recent studies reached different conclusions, any results probably would be specific to a particular situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Möller 1980, van der Veer 1985, Arai 1988, Bailey & Houde 1989, Shiganova 1998, virtually no direct comparisons of diet and co-occurrence have been made. Although 2 recent studies reached different conclusions, any results probably would be specific to a particular situation.…”
Section: Introductionmentioning
confidence: 99%
“…Species in the gelatinous genera Aurelia, Pleurobrachia, Cyanea, and Aequorea often occur in great abundance in the world's oceans (e.g. Hirota 1974, van der Veer 1985, Fancett 1988, Purcell & Grover 1990, Båmstedt et al 1997, Dawson & Martin 2001, Purcell et al 2001, Sparks et al 2001. Walleye pollock, Pacific herring and pink salmon are highly abundant fish species that support important commercial fisheries in various areas of the North Pacific Ocean; similarly, species of sandlance and herring are fished in several northern oceans (FAO 1999a,b, National Marine Fisheries Service 1999.…”
Section: Introductionmentioning
confidence: 99%
“…The scyphomedusa Aurelia aurita or the hydromedusae Rathkea octopunctata and Sarsia tubulosa are dominant jellyfish species in several neritic ecosystems (van der Veer 1985, Matsakis & Conover 1991, Kopacz 1994, including Limfjorden, and were therefore selected for clearance measurements. A single measurement of the clearance rate of Bougainvillia superciliaris was also made.…”
Section: Introductionmentioning
confidence: 99%
“…They spawn at night (Ferraro 1980), thus maximizing the dispersal of the spawning products before visual predators can recognize the egg patches. There also seems to be a tendency towards spawning and hatching before the blooms of gelatinous plankton (van der Veer 1985;Bailey and Houde 1989). However, this is probably not an adaptive reproductive strategy, but rather an indication that other planktonic zooplankton organisms occurring later in the season are the main prey organisms of gelatinous predators.…”
Section: -10 Days Post Hatching --------= -mentioning
confidence: 98%
“…However, this is probably not an adaptive reproductive strategy, but rather an indication that other planktonic zooplankton organisms occurring later in the season are the main prey organisms of gelatinous predators. Spatial separation of fish eggs and larvae and their predators also seems to be important (Bailey and Yen 1983;Frank and Leggett 1985;van der Veer 1985). Mass hatching in capelin was studied by Frank and Leggett (1982) and they concluded that this could be another strategy and have a positive effect due to "swamping" and satiation of predators.…”
Section: -10 Days Post Hatching --------= -mentioning
confidence: 99%